Intensive versus less-intensive antileukemic therapy in older adults with acute myeloid leukemia: A systematic review. - Yaping Chang; Gordon H Guyatt; Trevor Teich; Jamie L Dawdy; Shaneela Shahid; Jessica K Altman; Richard M Stone; Mikkael A Sekeres; Sudipto Mukherjee; Thomas W LeBlanc; Gregory A Abel; Christopher S Hourigan; et al. (PLoS ONE, 2021)
To compare the effectiveness and safety of intensive antileukemic therapy to less-intensive therapy in older adults with acute myeloid leukemia (AML) and intermediate or adverse cytogenetics, we searched the literature in Medline, Embase, and CENTRAL to identify relevant studies through July 2020. We reported the pooled hazard ratios (HRs), risk ratios (RRs), mean difference (MD) and their 95% confidence intervals (CIs) using random-effects meta-analyses and the certainty of evidence using the GRADE approach. Two randomized trials enrolling 529 patients and 23 observational studies enrolling 7296 patients proved eligible. The most common intensive interventions included cytarabine-based intensive chemotherapy, combination of cytarabine and anthracycline, or daunorubicin/idarubicin, and cytarabine plus idarubicin. The most common less-intensive therapies included low-dose cytarabine alone, or combined with clofarabine, azacitidine, and hypomethylating agent-based chemotherapy. Low certainty evidence suggests that patients who receive intensive versus less-intensive therapy may experience longer survival (HR 0.87; 95% CI, 0.76-0.99), a higher probability of receiving allogeneic hematopoietic stem cell transplantation (RR 6.14; 95% CI, 4.03-9.35), fewer episodes of pneumonia (RR, 0.25; 95% CI, 0.06-0.98), but a greater number of severe, treatment-emergent adverse events (RR, 1.34; 95% CI, 1.03-1.75), and a longer duration of intensive care unit hospitalization (MD, 6.84 days longer; 95% CI, 3.44 days longer to 10.24 days longer, very low certainty evidence). Low certainty evidence due to confounding in observational studies suggest superior overall survival without substantial treatment-emergent adverse effect of intensive antileukemic therapy over less-intensive therapy in older adults with AML who are candidates for intensive antileukemic therapy.